SNX9 Inhibits Cell Proliferation and Cyst Development in Autosomal Dominant Polycystic Kidney Disease via Activation of the Hippo-YAP Signaling Pathway - Shen, Ai-Wen; Fu, Li-Li; Lin, Lu; Sun, Bo; Song, Dong-Xu; Wang, Wu-Tao; Wang, Yi-Hao; Yin, Pei-Ran; Yu, Sheng-Qiang (Frontiers in Cell and Developmental Biology, 2020)
Autosomal dominant polycystic kidney disease (ADPKD) is a complex process, involving the alteration of multiple genes and signaling pathways, and the pathogenesis of ADPKD remains largely unknown. Here, we demonstrated the suppressive role of sorting nexin 9 (SNX9) during ADPKD development. SNX9 expression was detected in the kidney tissues of ADPKD patients, for the first time, and SNX9 expression was also detected in Pkd1 knockout (Pkd1-/-) and control mice. Subsequently, a series of gain- and loss-of-function studies were performed, to explore the biological roles and underlying molecular mechanisms of SNX9 in ADPKD progression. The expression of SNX9 was significantly downregulated in ADPKD patients and Pkd1-/- mice compared with control individuals and wild-type mice (Pkd1+/+), respectively. The ectopic expression of SNX9 significantly inhibited ADPKD cell proliferation, renal cyst formation and enlargement, whereas these effects were promoted by SNX9 silencing. Mechanistically, we found that SNX9 interacted directly with yes-associated protein (YAP) and increased the large tumor suppressor kinase 1 (LATS1)-mediated phosphorylation of YAP, resulting in the cytoplasmic retention of YAP, the decreased transcriptional activity of the YAP/TEA domain transcription factor 4 (TEAD4) complex, and, consequently, the inhibition of Hippo target gene expression and ADPKD development. Taken together, our findings provided novel insights into the role played by SNX9 during ADPKD pathogenesis and may reveal novel therapeutic approaches for ADPKD and related kidney diseases.